2022
DOI: 10.1002/anie.202208436
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Length Control in Nonchelated d8‐Metallosupramolecular Polymers through Metal‐Metal Interactions

Abstract: Supramolecular polymers (SPs) of d8 transition metal complexes have received considerable attention by virtue of their rich photophysical properties arising from metal‐metal interactions. However, thus far, the molecular design is restricted to complexes with chelating ligands due to their advantageous preorganization and strong ligand fields. Herein, we demonstrate unique pathway‐controllable metal‐metal‐interactions and remarkable 3MMLCT luminescence in SPs of a non‐chelated PtII complex. Under kinetic contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 75 publications
(134 reference statements)
1
25
0
Order By: Relevance
“…In particular, a nonemissive H-aggregate was formed from a rapid, kinetically controlled cooperative assembly assisted by 4fold hydrogen-bonding interactions, while the thermodynamic controlled self-assembly was assisted by extended Pt•••Pt interactions accompanied by MMLCT emission. 235 Due to the kinetically trapped assemblies, the sequential and controlled synthesis of Pd(II) and Pt(II) supramolecular block copolymers has been explored by Che, in which the manipulation of the kinetically trapped aggregates was found to be crucial to the formation of such a sequential block. 236 Distinctive from the aforementioned examples of the utilization of the single-component metal complex to obtain the kinetically trapped states by Manners (Figure 8), Yam adopted another strategy to realize the kinetics of the supramolecular assemblies by the utilization of two-component ensemble systems.…”
Section: ■ Kinetic Control Of Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a nonemissive H-aggregate was formed from a rapid, kinetically controlled cooperative assembly assisted by 4fold hydrogen-bonding interactions, while the thermodynamic controlled self-assembly was assisted by extended Pt•••Pt interactions accompanied by MMLCT emission. 235 Due to the kinetically trapped assemblies, the sequential and controlled synthesis of Pd(II) and Pt(II) supramolecular block copolymers has been explored by Che, in which the manipulation of the kinetically trapped aggregates was found to be crucial to the formation of such a sequential block. 236 Distinctive from the aforementioned examples of the utilization of the single-component metal complex to obtain the kinetically trapped states by Manners (Figure 8), Yam adopted another strategy to realize the kinetics of the supramolecular assemblies by the utilization of two-component ensemble systems.…”
Section: ■ Kinetic Control Of Nanostructuresmentioning
confidence: 99%
“…More recently, they also demonstrated pathway-controllable metal–metal interactions with MMLCT emission based on a non-preorganized, monodentate-ligand-containing platinum­(II) complex. In particular, a nonemissive H-aggregate was formed from a rapid, kinetically controlled cooperative assembly assisted by 4-fold hydrogen-bonding interactions, while the thermodynamic controlled self-assembly was assisted by extended Pt···Pt interactions accompanied by MMLCT emission . Due to the kinetically trapped assemblies, the sequential and controlled synthesis of Pd­(II) and Pt­(II) supramolecular block copolymers has been explored by Che, in which the manipulation of the kinetically trapped aggregates was found to be crucial to the formation of such a sequential block …”
Section: Kinetic Control Of Nanostructuresmentioning
confidence: 99%
“…1a, dotted orange line). 22 Analogously, different preparation methods were investigated for 2 (Fig. 1b, for details see Fig.…”
mentioning
confidence: 99%
“…[19][20][21] Recently, we have demonstrated that the inclusion of flexible bisamide hydrogen bonding synthons is a successful strategy to achieve PtÁ Á ÁPt contacts and 3 MMLCT with excimeric character in bispyridyldichlorido Pt(II) complexes upon SP (see complex 1, Scheme 1). 22 Given that halogens can have a significant impact on SP, 23,24 we herein investigate the hitherto unknown halogen effects on metal-metal interactions in singleand two-component SPs. We thus designed a new complex 2 with bulkier bromido ligands, keeping the molecular design unaltered.…”
mentioning
confidence: 99%
See 1 more Smart Citation